Between Management and Employees: Which one is More Critical in Building Value and Loyalty? - Lubis, Arief Wibisono; Halim, Rizal Edy (UI Scholars Hub, 2021)
We conducted a research concerning the relationship between trust, value, and loyalty based on the model developed by Sirdeshmukh et al. (2002). Confirmatory factor analysis and structural equation modeling were used to test the model. According to the model, the authors made a distinction between trustworthiness and trust dimension in Sales Promotion People (SPP) context and Management Policies and Practices (MPP) context. By collecting primary data from 105 respondents, the result shows that in the MPP context, operational benevolence was proven to demostrate a statistically significant positive effect to trust in MPP. Both the trust in MPP and trust in SPP dimensions have statistically significant positive effect in creating value, Trust in MPP and value dimensions have statistically significant positive effect to loyalty dimension. Moreover, from the result, it can be inferred that the role of MPP, rather than SPP was more critical in building consumers value and loyalty. The authors also found no asymmetric effect in the relationship between trustworthiness and trust dimension.